Circulating unmetabolized folic acid and 5-methyltetrahydrofolate and risk of breast cancer: a nested case-control study - Koenig, Karen L.; Scarmo, Stephanie; Afanasyeva, Yelena; Clendenen, Tess V.; Ueland, Per Magne; Zeleniuch-Jacquotte, Anne (European journal of clinical nutrition, 2020)
Background/Objectives Folates found in natural foods are thought to protect against cancer. However, folic acid (FA), a synthetic form of folate used in supplements and fortified foods, may increase breast cancer risk if present in unmetabolized form (UMFA) in the circulation. This study examined the associations of serum UMFA and 5-methyltetrahydrofolate (5-mTHF), the predominant form of circulating folate, with breast cancer risk. Subjects/Methods We conducted a nested case-control study in a prospective cohort. In total, 553 cases of invasive breast cancer, diagnosed before mandatory FA fortification of grain in the US in 1998, were individually-matched to 1059 controls. Serum UMFA and 5-mTHF were measured using liquid chromatography-tandem mass spectrometry in stored serum samples, and 5-mTHF was corrected for storage degradation. Results Serum UMFA was not associated with breast cancer risk: the percentage of women with detectable levels of UMFA was similar in cases and controls (18% and 20%, respectively; p = 0.46). Two tag-SNPs in the promoter region of the FA-metabolizing gene were also not associated with risk. There was a marginally significant inverse association of 5-mTHF corrected with breast cancer risk (odds ratio for the highest vs. lowest quintile = 0.69, 95% CI = 0.49 to 0.97; p trend = 0.08). Conclusions Circulating UMFA was not associated with breast cancer risk. These results apply to countries without mandatory FA food fortification. Studies are needed in countries with mandatory fortification, where levels of UMFA are much higher than in our study.